Current Scenario of Stiletto Flies (Insecta: Diptera: Therevidae) in India - Mitra, Bulganin; Roy, Sankarsan; Bhaumik, Subhrajit; Roy, Souradip; Halder, Sumana; Chakraborty, Anirban (Asian Journal of Biological and Life Sciences)
A total of 18 species of three genera under two subfamilies of the family Therevidae belonging to the order Diptera are reported from India which is only 1.57 % of total global therevid fauna. Among these, nine species have restricted their distribution within the country. But there is no sufficient information about the specific distributional localities of 38.88%of Indian therevids. Considering the biogeographic zones of India, the highest number of stiletto flies were found in the Himalayan regions (38.88%) and the least number from Arid, Semi-Arid & Hot desert region (5.55%). This is the first consolidated account on the current status of Indian therevid fauna.
Keywords: Bio-geographical Patterns; Biodiversity; India; Therevidae